PENGARUH KINERJA KARYAWAN, KUALITAS PELAYANAN, DAN KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN DI SELARAS COFFEE SHOP GEMOLONG - Mira Indri; Edi Purwanto; Dwinda Agustintia (JURNAL ILMIAH EDUNOMIKA, 2026)
Abstract The influence of employee performance, service quality, and product quality on customer satisfaction at Selaras Coffee Shop Gemolong can be concluded as follows: Employee Performance Has a Positive and Significant Influence on Customer Satisfaction. Service Quality Does Not Have a Significant Effect on Customer Satisfaction Partially. Product Quality Has a Positive and Significant Influence on Customer Satisfaction Employee Performance, Service Quality, and Product Quality Simultaneously Have a Significant Influence on Customer Satisfaction. Product Quality is the Most Dominant Variable Influencing Customer Satisfaction. The number of samples used in this study was 50 respondents, who were customers of Selaras Coffee Shop Gemolong. Keywords : employee performance, service quality, and product quality on customer satisfaction